THE SCIENTIFIC BASIS FOR ADOPTING PROCESS APPROACH IN TEACHING CHINESE WRITING SKILLS FOR SECOND-YEAR STUDENTS AT MILITARY SCIENCE ACADEMY (Journal of Foreign Language Studies, 2019)
Process approach is one of the important teaching methods in teaching languages in general and Chinese in particular. This approach emphasizes the crucial effects of the writing process, the editing stages and the practice between teachers and learners as well as among learners themselves. It also stresses the fostering of writing contents and expressions and the use of repeated corrections to improve learners’ writing skills. Within the scope of this theoretical and practical based study, the author uses the comparative method to provide some scientific foundations for adopting process approach. Thereby, the article helps teachers have a more thorough overview of process approach, teaching contents and learners to flexibly put it in practice; thus, improving the quality of teaching Chinese writing skills at Military Science Academy.
Keywords: scientific bases; process approach; Chinese writing skill; the second year; teaching methods